Foreleg Angle in Pig Carcasses as a Potential Indicator of Degree of Rigor Development and Meat Quality - Vasudevan, V. N.; Kutinarayanan, P.; Sathu, T.; Irshad, A.; Prajwal, S. (Journal of Meat Science, 2018)
The current study was conducted to assess the foreleg angle (FLA) in pig carcasses as a potential indicator of the degree of rigor development and correlate it with certain pork quality attributes. Sixteen cross-bred female Large White Yorkshire pigs (6-8 months, 90-100 kg) were humanely slaughtered and the FLA at 45 min post-slaughter for each carcass (held at about 35 oC) was determined by pictorial measurement. Meat samples were analysed for pH at 45 min post-slaughter (pHi), instrumental colour, drip loss, ultimate pH (pHu) and difference between pHi and pHu (ΔpH). FLA was significantly correlated (p120° and Group II: FLA
Keywords: Pig; Fore leg angle; Pre-slaughter stress; Pork quality